Development of Android-Based Management Information System Application for Student Final Project Services - Mukhammad Rivaldi Ghani; Dwi Sukma Donoriyanto (P3M Politeknik Negeri Bengkalis, 2025)
The final project service system in the Industrial Engineering Study Program at Universitas Pembangunan Nasional